Sistemas de implantação de milho em planossolos do Rio Grande do Sul - Giacomeli, Robson (2015)
Among the barriers to obtain satisfactory levels in grain yield of irrigated rice, it is highlighted weed resistance. Crop rotation with corn could be a good alternative to reduces seedbank, improves nutrient cycling and breaks the cycle of pathogens and pests.However, this crop presents difficulty to adapt in Planossolo, due presence of a compacted layer, water excess, and water deficit. The objectives of this study were to evaluate corn tillage systems in irrigated rice fields. The experiments was conducted in field conditions, in Planossolos of central region of the Rio Grande do Sul State during 2013/14 and 2014/15 seasons. The first experiment was conducted in order to evaluate sowing using shanks, sowing using double disks and sowing using notched disks on soil physics and corn growing, across different locations, Santa Maria and Formigueiro. In the second experiment it was evaluated soil physical parameters on different tillage systems deep tillage, conventional and no-till with raised bed and no-raised bed in two seasons. In both experiments, was evaluated soil physical parameters and explanatory variables in corn. It was observed satisfactory results in soil physical properties for the systems with more soil mobilization.The treatments with lower soil penetration resistance, airspace and macroporosity higher in the root system region produced higher grain yield. Deep tillage, no-till with sowing using shank and sowing with raised bed are the best alternatives to corn sowing in Planossos in irrigated rice fields